One-year clinical outcomes of patients implanted with a Resolute Onyx™ zotarolimus-eluting stent - Chor Cheung Tam; Kelvin Chan; Simon Lam; Arthur Yung; Yui Ming Lam; Carmen Chan; David Siu; Hung Fat Tse (Journal of International Medical Research, 2018)
Objective To evaluate the 1-year clinical outcomes of patients who received the Resolute Onyx™ stent. Methods This was a single-centre, retrospective registry analysis that reviewed the clinical data from all patients who were implanted with a Resolute Onyx™ stent between March 2015 and February 2016. Clinical follow-up was performed at 1 year post-implantation. Results A total of 252 patients received a Resolute Onyx™ stent and two patients were lost to follow-up. The mean age of the cohort was 66.9 years and 113 (45.2%) had diabetes mellitus. Thirty-eight patients (15.2%) had left main disease and 73 (29.2%) had three-vessel disease. A total of 175 patients (70.0%) had small vessel disease (<2.75 mm) and 210 (84.0%) had long lesions (>20 mm). The 1-year target lesion failure was 4.4% (11 of 250), cardiovascular death occurred in eight patients (3.2%), ischaemia-driven target lesion revascularization was undertaken in five patients (2.0%) and stent thrombosis occurred in one patient (0.4%). Conclusion The Resolute Onyx™ stent showed a favourable 1-year clinical performance in a real-world population.